Sleep duration and cardiovascular disease risk in type 2 diabetes: A prospective cohort study - Zhi Jin; Haiyan Wang; Hai Bin Wen (PLoS ONE, 2025)
Background Cardiovascular disease (CVD) remains the leading cause of mortality in Type 2 Diabetes Mellitus (T2DM) patients. While sleep duration has emerged as a potential modifiable risk factor for CVD, evidence from prospective studies among T2DM patients remains scarce and inconsistent. We aimed to investigate the association between sleep duration and incident CVD risk among Chinese adults with T2DM. Methods We conducted a prospective cohort study using data from the China Health and Retirement Longitudinal Study (CHARLS) (2015–2018). Sleep duration was assessed through validated questionnaires at baseline. Incident CVD was defined as the first occurrence of physician-diagnosed coronary heart disease, stroke, or heart failure during follow-up. Logistic regression models were employed to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for the risk of CVD, with adjustments made for potential confounding variables. Results Among 1,360 participants with T2DM, the mean sleep duration was 6.45 ± 1.95 hours. During follow-up, 237 (17.43%) participants reported new-onset CVD. In the fully adjusted model, a significant inverse association was found between sleep duration and CVD risk (OR: 0.92, 95% CI: 0.86–0.99, P = 0.03). Notably, individuals with long sleep duration (>9 hours) had a significantly decreased risk of CVD (OR: 0.36, 95% CI: 0.15–0.85, P = 0.02) compared to those with shorter sleep durations. Conclusion Our findings indicate an inverse association between sleep duration and the risk of new-onset cardiovascular disease in Chinese adults with type 2 diabetes mellitus, with longer sleep duration associated with lower CVD risk.